Juridical Study of Agreements Between Developers and Home Buyers in Failed to Build Issues - Yuliani, Nur Amanah; Dwi Istinah, Siti Rodhiyah (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The purpose of this study is to analyze: 1). Implementation of the agreement between the developer and the buyer of the house in the problem of failing to build in Pemalang City at this time. 2). Implementation of the agreement between the developer and the buyer of the house in the case of failing to build in Pemalang City, which should be. The approach method in this research is a normative juridical approach using a statutory approach and a conceptual approach. The secondary data used were obtained through literature study, data analysis was carried out using descriptive analytic. The results of the study concluded: 1). The problem of failure to build usually only arises when the object in the house sale and purchase agreement has been handed over, but it turns out that the quality is not as expected by the consumer or the environment where the house that is the object of the agreement is built is not in accordance with the agreement. This is actually something that needs to be looked at together both by the developer himself as a seller and by the consumer as a buyer. In addition, failure to wake up late is known when the handover of the house is carried out during the dry season and consumers only find out that there will be defects in the building during the rainy season. Even though the warranty period from the developer has expired. This problem is experienced by consumers from CV. Bima Abadi then filed a complaint to the developer about the problem. In the end, the matter was resolved amicably. The parties agree that the developer will bear the cost of destroying the building in half and the rest will be borne by the consumer. 2). The implementation of the agreement should be based on contractual liability (responsibility based on the agreement) as regulated in article 134 of Act No. 1 of 2011 concerning Housing and Settlement Areas which states that